Training in Composting Efforts to Develop Economically Value Compost Products by Family Welfare Empowerment (FWE) Batuan Village, Sukawati District, Gianyar District, Bali - I Nengah Muliarta; Ni Luh Putu Putri Setianingsih; I Wayan Sudiarta; Desak Ayu Diah Prawerti; I Kadek Somariana; I Ketut Suwarmadi Putra (East Asian Journal of Multidisciplinary Research, 2023)
The Community Service Activities Conducted in Batuan Village, Sukawati, and Gianyar-Bali Aim to Increase Knowledge and Skills of Family Welfare Empowerment (FWE) In Managing Composting to Become Fertilizer Products That Have Economic Value. FWE has become a leader in waste management at the household level. The methods used include observation, counseling or education, direct practice, monitoring, and evaluation. Based on the results, 100% of FWE can use tools for the composting process to produce organic compost with economic value, 100% understand the use of compost, and 100% are skilled in using compost as quality organic compost. FWE in Batuan Village, after receiving socialization and training, commits to sorting waste and making compost into organic fertilizer with economic value.